Inhibitory Activity of Polypodium feei Root Extracts on Nitric Oxide and TNF-α Synthesis in LPS‐activated RAW264.7 Cell Line - Suwandi, Deden Winda; Hamdani, Siva; Ruchiyat, Ruchiyat (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Polypodium feei (P. feei) roots have been reported to contain sellegueain A, a compound with analgesic and anti-inflammatory properties demonstrated in experimental animals. However, the anti-inflammatory activity of extracts, which represent the form most used in traditional medicine, has not been scientifically validated. This study aims to test the anti-inflammatory activity of P. feei root extract in inhibiting the synthesis of inflammatory mediators such as NO, iNOS, and TNF-α in RAW264.7 macrophage cells stimulated by lipopolysaccharide (LPS). RAW264.7 cells were used to evaluate the inhibitory activity of test compounds on the production of inflammatory mediators NO, iNOS, and TNF-α. Research parameters included cell viability testing with MTS, colorimetric test to determine the concentration of nitric oxide (NO), ELISA test to measure protein levels of the iNOS and TNF-α. P. feei root extract at concentrations of 10, 50, 100, and 150 µg/mL inhibited the production of inflammatory mediators with the best activity in inhibiting NO and iNOS with IC50 values of 87.22 and 99.99 µg/mL, respectively. This study shows that P. feei root extract has anti-inflammatory activity through inhibiting the production of NO, iNOS and TNF-α mediators in LPS-stimulated RAW264.7 macrophage cells.